2020
DOI: 10.1155/2020/8881405
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Outcomes of Microfragmented Adipose Tissue Treatments of Knee Osteoarthritis: An Observational, Intention-to-Treat Study at Twelve Months

Abstract: Introduction. Microfragmented adipose tissue (MFAT) has been shown to benefit osteoarthritic patients by reducing pain and supporting tissue regeneration through a mesenchymal stem cell (MSC)-related paracrine mechanism. This observational study of 110 knees assessed patient-centered outcomes of pain, functionality, and quality of life, analyzing their variation at twelve months following one ultrasound-guided intra-articular injection of autologous MFAT for the treatment of knee osteoarthritis (KOA). Method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Several previous studies have looked at the expression profiles of cytokines released by MFAT and SVF in a culture [ 6 ] although only using available commercial arrays and showed the MFAT expression of angiogenic factors such as the placental growth factor and angiogenin as well as HGF (shown in our data here also) and PDGF growth factors and other inflammation associated molecules such as IL-13, 3, 16 and 27. Their purpose was to compare the secretion against that of SVF and whilst MFAT was clearly more active in its secretion profile the comparisons failed to include key markers that defined the capability of MFAT; for example, to reduce pain and support the repair of or regeneration in joints with osteoarthritis [ 16 ]. Here, we have constructed an array that identified the major players, demonstrating a very high expression of the critical anti-inflammatory protein IL1-Rα antagonist, the major ‘protector’ against Il-1 signalling, which is the critical inflammatory pathway activated during the development of O/A and blocking, which has been shown to nullify multiple connected inflammatory pathways in disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have looked at the expression profiles of cytokines released by MFAT and SVF in a culture [ 6 ] although only using available commercial arrays and showed the MFAT expression of angiogenic factors such as the placental growth factor and angiogenin as well as HGF (shown in our data here also) and PDGF growth factors and other inflammation associated molecules such as IL-13, 3, 16 and 27. Their purpose was to compare the secretion against that of SVF and whilst MFAT was clearly more active in its secretion profile the comparisons failed to include key markers that defined the capability of MFAT; for example, to reduce pain and support the repair of or regeneration in joints with osteoarthritis [ 16 ]. Here, we have constructed an array that identified the major players, demonstrating a very high expression of the critical anti-inflammatory protein IL1-Rα antagonist, the major ‘protector’ against Il-1 signalling, which is the critical inflammatory pathway activated during the development of O/A and blocking, which has been shown to nullify multiple connected inflammatory pathways in disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results of the largest published MFAT series to date ( n = 110 knees), patient reported outcome measures VAS, OKS, and EQ-5D score all improved in statistically significant ways at 12 months follow-up [ 37 ]. However, in contrast to our study, no adverse events were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue was harvested and microfragmented using previously published technique [ 9 ]. The MFAT was then injected under ultrasonographic guidance into the knee joint.…”
Section: Methodsmentioning
confidence: 99%
“…Microfragmented adipose tissue (MFAT) is one such therapy and is being increasingly explored for its benefit in managing OA. Cell-based therapies have demonstrated potential in treating OA [ 8 , 9 ]. Mesenchymal stem cells (MSCs), derived from MFAT, can transform into cartilage, adipocytes, osteoblasts, and osteocytes [ 10 ]; inhibit T cell growth [ 11 ]; and encourage joint repair through cartilage regeneration and inflammatory downregulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation